Beautiful losers [videorecording (DVD)] - Rose, Aaron; Leonard, Joshua; Campbell, Thomas, 1969-; Fairey, Shepard; Kilgallen, Margaret, 1967-2001; McGee, Barry, 1966- (Oscilloscope Pictures, 2009)
Follows the lives and careers of a group of artists and designers who inadvertantly affected the art world.